Dental Faculty Experiences of Drug Prescription Patterns: A Qualitative Study - Nader Navabi; Nahid Karbasi; Fatemeh Najminouri; Mahsa Malek-Mohammadi; Mohammad Amin Roshan Pour (Kerman University of Medical Sciences, 2023)
Background: Dental prescribing is considered a basis for short-term treatment of clinical problems. Therefore, dentists should be familiar with the patterns of rational drug prescription. Neglecting this important issue can lead to misprescription and side effects. Accordingly, the present study aimed to investigate the experiences of a group of dental specialists about prescribing drugs.Methods: This qualitative study was conducted using a conventional content analysis approach. A total of 19 specialists from 5 different fields (oral diseases, pediatric dentistry, oral and maxillofacial surgery, endodontics, and periodontics) participated in this study. Purposive and theoretical sampling was used to collect data and semi-structured in-depth interviews were conducted in the form of focus group discussions from each department at Kerman dental school. Data collection and content analysis were performed simultaneously. Results: The analysis of the data revealed five categories including more frequently prescribed drugs, common concerns about prescribing drugs, recommendations for reducing potential side effects, experience of clinical pharmacology training, and criteria for prescribing new drugs.Conclusion: Since the knowledge of dental students affects the quality and effectiveness of treatment and patient safety, this study emphasized the need to improve clinical pharmacology training provided to dentistry students, residents, and dentists.